Relation between intra-abdominal pressure and early intestinal ischemia in rats. Issue 1 (1st December 2020) - Strang, Steven G; van der Hoven, Ben; Monkhorst, Kim; Ali, Samir; van Lieshout, Esther M M; van Waes, Oscar J F; Verhofstad, Michael H J
Abstract : Background: Little is known on early irreversible effects of increased intra-abdominal pressure (IAP). Therefore, timing of abdominal decompression among patients with abdominal compartment syndrome remains challenging. The study objective was to determine the relation between IAP and respiratory parameters, hemodynamic parameters, and early intestinal ischemia. Methods: Twenty-five anesthetized and ventilated male Sprague-Dawley rats were randomly assigned to five groups exposed to IAPs of 0, 5, 10, 15, or 20 mm Hg for 3 hours. Respiratory parameters, hemodynamic parameters, and serum albumin-cobalt binding (ACB) capacity as measure for systemic ischemia were determined. Intestines were processed for histopathology. Results: IAP was negatively associated with mean arterial pressure at 90 (Spearman correlation coefficient; Rs=−0.446, p=0.025) and 180 min (Rs=−0.466, p=0.019), oxygen saturation at 90 min (Rs=−0.673, p<0.001) and 180 min (Rs=−0.882, p<0.001), and pH value at 90 (Rs=−0.819, p<0.001) and 180 min (Rs=−0.934, p<0.001). There were no associations between IAP and lactate level or ACB capacity. No histological signs for intestinal ischemia were found. Discussion: Although increasing IAP was associated with respiratory and hemodynamic difficulties, no signs for intestinal ischemia were found. Level of evidence: Prognostic and epidemiologic study, level II.